Farmers' Constitutional Rights and Subsidized Fertilizer: How is the State Responsible? - Yuwono, Nurbaity Prastyananda; Munajad, Dias Said (Asian Journal of Law and Humanity, 2024)
Fertilizers play an essential role in increasing agricultural productivity, and Indonesia has implemented a subsidized fertilizer policy since the 1970s to alleviate the burden on farmers and provide fertilizers at affordable prices. However, farmers often face scarcity and difficulties in obtaining subsidized fertilizers, despite their constitutional rights being stipulated in the Minister of Trade Regulation Number 15/MDAG/PER/4/2013 regarding the procurement and distribution of subsidized fertilizers. This research uses an empirical legal method, with primary data obtained through interviews with farmers in Sokoduwet Village, Pekalongan, and secondary data sourced from related documents and literature. Data collection techniques include observation, interviews, and documentation. The study aims to assess the fulfillment of farmers' constitutional rights in obtaining subsidized fertilizers and to understand the legal consequences of fulfilling these rights. The findings indicate that farmers' constitutional rights in Sokoduwet Village have been fairly fulfilled, as subsidized fertilizers help reduce their burden and production costs. However, issues of fertilizer scarcity persist during planting periods, necessitating improvements from distributors and the government to ensure a smoother distribution process. Existing regulations and government decrees have provided farmers with guaranteed rights, including easier access through Farmer Cards and Farmer Identification.